2017
DOI: 10.1371/journal.pone.0185314
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of atherosclerotic stenosis determining early neurologic deterioration in acute ischemic stroke

Abstract: Background and purposeEarly neurologic deterioration (END) during the acute stage of stroke is clinically important because of its association with poor outcomes. The purpose of this study was (1) to investigate variables associated with END, (2) to determine the distribution of atherosclerotic stenosis associated with END, and (3) to clarify the relationship between END and clinical outcomes.Methods516 patients with acute ischemic stroke were included. The median follow-up period was 31.7 months. END was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“… 9 Cerebral artery stenosis (which is closely related to recurrent stroke), stroke progression, and END were found to be independently associated with IABD in patients with noncardioembolic stroke. 31 Our findings support the results of these previous studies; moreover, because END could produce a poor long-term prognosis in stroke patients, our results may provide additional evidence for the association between IABD and a poor long-term prognosis. Our study further suggests that bilateral brachial blood pressure measurements provide an easy screening tool for estimating the probability of END in acute noncardioembolic stroke patients.…”
Section: Discussionsupporting
confidence: 92%
“… 9 Cerebral artery stenosis (which is closely related to recurrent stroke), stroke progression, and END were found to be independently associated with IABD in patients with noncardioembolic stroke. 31 Our findings support the results of these previous studies; moreover, because END could produce a poor long-term prognosis in stroke patients, our results may provide additional evidence for the association between IABD and a poor long-term prognosis. Our study further suggests that bilateral brachial blood pressure measurements provide an easy screening tool for estimating the probability of END in acute noncardioembolic stroke patients.…”
Section: Discussionsupporting
confidence: 92%
“…Third, this positive association may depend on the underlying vascular lesions. In general, patients with ischemic stroke due to LAA mechanisms have worse early outcomes,[11, 12, 35] and the burden of stenotic lesions or stability of atherosclerotic plaques seem to have important roles. [11, 27, 3537] Previous studies have revealed that serum NLR levels are associated with the burden of ICAS and ECAS in a dose-response manner.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ischemic stroke due to large-artery atherosclerosis (LAA) are prone to early neurological deterioration (END), and thus have worse clinical outcomes. [11, 12] In the acute phase after ischemic stroke, circulating neutrophils are immediately recruited to the ischemic areas, where they secret destructive materials (e.g., reactive oxygen species, proteases, matrix metalloproteinase-9, and cytokines) into neural tissues. [7, 1315] At the same time, relative lymphopenia develops, partly in response to stress-induced corticosteroids, which attenuates IL-10-mediated healing process after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…32,39 In the current study, it was worth noting that a personal history of stroke was a distinct and crucial factor that significantly increased the incidence of ICAS; correspondingly, early neurologic worsening in the phase of ischemic stroke could be determined pre-stroke by the distribution of ICAS subtype. 15,40 Consequently, a healthy lifestyle, regular physical examination and effective primary prevention measures are indispensable. 22…”
Section: Discussionmentioning
confidence: 99%